General music teachers' attitudes and practices regarding multicultural music education in Malaysia. (2nd April 2016) - Wong, Kwan Yie; Pan, Kok Chang; Shah, Shahanum Mohd
Abstract : This study examined the utilisation of multicultural music education by Malaysian music teachers, with an emphasis on the relationship between music teachers' attitudes and their subsequent degree of effort in developing and implementing multicultural music education in their music classes. Respondents for the study were 456 music teachers; responses were collected via an adapted version of the original Music Specialist's Multicultural Music Education Survey instrument. Results indicate that there is limited implementation of multicultural music education in music classrooms due to inadequate preparation and limited resources and insufficient knowledge of multicultural music. As such, music teacher training programmes are needed in order to address both the theoretical and practical aspects of multicultural music education throughout the curriculum in a comprehensive and long-term manner.